A short history of film - Dixon, Wheeler W., 1950- (Rutgers University Press, 2018)
With more than 250 images, new information on international cinema--especially Polish, Chinese, Russian, Canadian, and Iranian filmmakers--an expanded section on African-American filmmakers, updated discussions of new works by major American directors, and a new section on the rise of comic book movies and computer generated special effects, this is the most up to date resource for film history courses in the twenty-first century.
Includes glossary of film terms.
Keywords: Motion pictures -- History.; Motion picture industry -- History.; Cinéma -- Histoire.; Cinéma -- Industrie -- Histoire.; PERFORMING ARTS -- Reference.; Motion picture industry; Motion pictures; History